2010
DOI: 10.1007/s11240-010-9851-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of Paphiopedilum orchid through formation of protocorm-like bodies

Abstract: Paphiopedilum orchids are among the world's most popular orchid due to their impressively beautiful flowers. Propagation of these orchid genera has been hampered by the naturally slow growth rate of the plant, which renders it very difficult to be propagated through conventional methods. In vitro culture techniques have provided a useful alternative technology for propagating this recalcitrant species. In this study, the propagation of P. rothschildianum was achieved through the in vitro formation of secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 38 publications
3
50
0
2
Order By: Relevance
“…It has been previously reported that the presence of 20% CW in tissue culture media were effective for PLBs growth and plantlet regeneration (Ng and Saleh, 2010). This natural compound is rich in cytokinins that are mostly used for PLB multiplication in the plant tissue culture…”
Section: Effects Of Chitosan On Leaf Organogenesismentioning
confidence: 99%
“…It has been previously reported that the presence of 20% CW in tissue culture media were effective for PLBs growth and plantlet regeneration (Ng and Saleh, 2010). This natural compound is rich in cytokinins that are mostly used for PLB multiplication in the plant tissue culture…”
Section: Effects Of Chitosan On Leaf Organogenesismentioning
confidence: 99%
“…Interestingly, SEM analysis of anterior meristematic pole of PLB showed elongated cone-shaped meristematic dome (Figure 2a and b). A more intense meristematic activity at one side of the dome displaced the apical end forming a hook-like structure depicting differentiated cells that are regarded as orchid embryos (Ng & Saleh, 2011) which develop with two discrete bipolar structures, where the upper region becomes the shoot while the bottom region becomes the root meristem (Jones, 2009). A notable anterior pole and posterior pole was observed on the PLB (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…The bipolar PLB eventually differentiated anterior and posterior regions into shoot and root system respectively (Figure 1d). Thus, meristematic PLB can be induced to regenerate into whole plantlets on plant growth regulator (PGR)-free medium (Ng & Saleh, 2011). Furthermore, the shoots develop directly from the primary and secondary meristems of PLB without an intervening explantorganogenesis phase (Ng & Saleh, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is partly due to their ability to proliferate rapidly [4]. Furthermore, PLBs can regenerate into complete plantlets in plant growth regulator free medium due to their bipolar nature which develop into shoot and root meristems [5].…”
Section: Introductionmentioning
confidence: 99%